Challenges and Opportunities in Internal Auditing in Public Institutions and Agricultural Companies: A Qualitative Approach through Focus-Group Method - Andrei Bogdan POPESCU-GRĂDIȘTEANU; Dorina MOCUȚA (Revista de Management Comparat International)
This paper examines the challenges and opportunities associated with internal auditing in public institutions and agricultural businesses. The study uses focus group methodology, involving six participants from various agricultural entities, to gain a detailed understanding of their perceptions and experiences. The analysis focuses on the efficiency and effectiveness of internal audit procedures, identifying both the strengths and weaknesses of these processes, as well as specific challenges and opportunities for improvement. It also discusses the impact of the particularities of the agricultural sector, such as seasonality and volatile climatic conditions, on the internal audit process. The results reveal that agricultural institutions face significant challenges, including excessive bureaucracy and limited resources, but also considerable opportunities through the use of advanced technologies and standardization of procedures.